Information management to succeed in making marketing decisions - Lombana González, María Emma
In a globalized world in continuous change, companies that want to achieve sustainable competitive advantages should be aware that the information is the most valuable strategic resource of the company, as it is the core of decision-making. This review article presents a comparative analysis between the concepts that have a significant impact in the decision-making process for the management of marketing, in current organizations: information system, business intelligence, research market and technological surveillance.For this a search, organization and analysis of documents was carried out that allowed compiling conceptual information through a comparative chart, which summarizes the basic terms and how complement each other to achieve decision-making successful in marketing management by individuals and companies interested therein, with minimal knowledge and little experience in these areas of learning. Throughout the article each of the concepts, following a same thread are described in depth: what is in itself, why it is important in marketing and how to apply it. The most outstanding item product of the article is building a conceptual comparison chart, which aims to differentiate each term and clearly establish the "synergistic" relationship between them for a successful decision making process.